2022
DOI: 10.1111/lang.12543
|View full text |Cite
|
Sign up to set email alerts
|

Generalizing Knowledge of Second Language Collocations: The Roles of Within‐ and Cross‐Language Similarity on Acceptability and Event‐Related Potentials

Abstract: Recent research has shown that knowledge of second language (L2) collocations is important to learners for improving their language processing and production but also that acquiring L2-specific collocations is a very burdensome task for learners. Thus, bootstrapping knowledge of L2 collocations through generalization is highly desirable, but this area has received surprisingly limited attention. This study examined L2 learners' ability to generalize knowledge of recently learned verb-noun collocations during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Although results reported by Pulido (2023) suggested that exposure to only one related collocation might result in generalization, repeated exposure to multiple collocations containing the same node might be more beneficial for collocation learning. This raises the question of how repeated encounters with multiple collocations for the same node should be distributed to maximize the benefits.…”
Section: Literature Reviewmentioning
confidence: 89%
See 3 more Smart Citations
“…Although results reported by Pulido (2023) suggested that exposure to only one related collocation might result in generalization, repeated exposure to multiple collocations containing the same node might be more beneficial for collocation learning. This raises the question of how repeated encounters with multiple collocations for the same node should be distributed to maximize the benefits.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The results of the acceptability judgement task indicated that repeated exposure to only one related collocation might have allowed participants to successfully generalize their knowledge of previously learned collocations to novel collocations. 1 Although results reported by Pulido (2023) suggested that exposure to only one related collocation might result in generalization, repeated exposure to multiple collocations containing the same node might be more beneficial for collocation learning. This raises the question of how repeated encounters with multiple collocations for the same node should be distributed to maximize the benefits.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations